Methodologies help you get it all in place at once - Stellman, Andrew; Greene, Jennifer, 1971- (O'Reilly, 2018)
This lesson describes the core agile values. It shows an example of a team struggling with a software project, and help you recognize that a main source of the struggle is a "fractured perspective." We'll explain the agile values, and use a metaphor to help you see how those values bring the team's perspective together.